1997
DOI: 10.1007/s002469900176
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Approach to Balloon Aortic Valvuloplasty in Infants with Critical Aortic Valve Stenosis

Abstract: We compare the clinical efficacy of two approaches for balloon aortic valvuloplasty (BAV) in infants with critical aortic valve stenosis. The approaches were through the carotid artery and the femoral artery. Eight catheterizations for BAV were performed in seven consecutive patients with critical aortic stenosis: four BAVs were approached through the femoral artery and four through the right common carotid artery. We inserted a 5F sheath into the right common carotid artery by a cutdown procedure; after BAV t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 5 publications
1
22
0
2
Order By: Relevance
“…This approached was considered when there are problems in femoral or umbilical catheterization approach 34. Many previous studies had demonstrated the use of carotid artery approach to BAV 35,36…”
Section: Discussionmentioning
confidence: 99%
“…This approached was considered when there are problems in femoral or umbilical catheterization approach 34. Many previous studies had demonstrated the use of carotid artery approach to BAV 35,36…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial description of balloon aortic valvuloplasty in the neonate by Lababidi and Weinhaus [12], several groups of workers [6][7][8][9][10][11][13][14][15][16][17][18][19][20][21] have adopted the technique and have reported reasonably good results. Whereas Lababidi and Weinhaus [12] performed the procedure by cut-down of the femoral artery, most workers prefer percutaneous transfemoral, transumbilical, or carotid artery retrograde or anterograde transfemoral venous techniques.…”
Section: Discussionmentioning
confidence: 99%
“…1 As first described in children by Azzolina et al 2 in 1973, surgical carotid cutdown involved placement of a purse-string suture, followed by creation of a longitudinal arteriotomy through which catheters were placed, and tying of the purse-string suture at the end of the case. Although this approach has been widely used and is considered to be safe and effective, [3][4][5][6] it is invasive, time consuming, requires an available surgeon, and results in scarring that is cosmetically less appealing and could complicate repeat vascular access in the same vessel.…”
mentioning
confidence: 99%